Sialoglycans on lymphatic endothelial cells augment interactions with Siglec‐1 (CD169) of lymph node macrophages. Issue 11 (26th October 2021) - D'Addio, Marco; Frey, Jasmin; Tacconi, Carlotta; Commerford, Catharina D.; Halin, Cornelia; Detmar, Michael; Cummings, Richard D.; Otto, Vivianne I.
Abstract: Cellular interactions between endothelial cells and macrophages regulate macrophage localization and phenotype, but the mechanisms underlying these interactions are poorly understood. Here we explored the role of sialoglycans on lymphatic endothelial cells (LEC) in interactions with macrophage‐expressed Siglec‐1 (CD169). Lectin‐binding assays and mass spectrometric analyses revealed that LEC from human skin express more sialylated glycans than the corresponding blood endothelial cells. Higher amounts of sialylated and/or sulfated glycans on LEC than BEC were consistently observed in murine skin, lung and lymph nodes. The floor LEC of the subcapsular sinus (SCS) in murine lymph nodes (LN) displayed sialylated glycans at particularly high densities. The sialoglycans of LN LEC were strongly bound by Siglec‐1. Such binding plays an important role in the localization of Siglec‐1 + LN‐SCS macrophages, as their numbers are strongly reduced in mice expressing a Siglec‐1 mutant that is defective in sialoglycan binding. The residual Siglec‐1 + macrophages are less proliferative and have a more anti‐inflammatory phenotype. We propose that the densely clustered, sialylated glycans on the SCS floor LEC are a key component of the macrophage niche, providing anchorage for the Siglec‐1 + LN‐SCS macrophages.